Assessment of Lead‐Free .22 LR Bullets for Shooting European Rabbits. (23rd September 2020) - Hampton, Jordan O.; DeNicola, Anthony J.; Forsyth, David M.
ABSTRACT: In response to health threats posed by toxic lead to humans and scavenging wildlife, there is currently a focus on transitioning from lead‐based to lead‐free bullets for shooting (harvesting, culling, or recreational hunting) of wild animals. However, the efficacy of lead‐free bullets for shooting small mammals has seldom been evaluated. We compared the animal welfare outcomes and costs of using lead‐based and lead‐free bullets in the world's most popular cartridge, the rimfire .22 LR, for shooting wild European rabbits ( Oryctolagus cuniculus ) in Australia, during August 2019. Ballistic testing revealed that lead‐free bullets were less precise than one type of commonly used lead‐based bullet when shot from one rifle. We shot at 53 and 115 rabbits with lead‐based and lead‐free bullets, respectively. A substantially lower percentage of rabbits that were hit were wounded (2%) with lead‐based bullets compared with lead‐free bullets (20%). Hence, fewer shots were needed to kill rabbits with lead‐based (1.27) than lead‐free (3.98) bullets. Radiographic examination of 28 rabbits shot with lead‐based bullets and 27 rabbits shot with lead‐free bullets revealed metallic fragments present in 82% and 41% of carcasses, respectively. In 52% of rabbits shot with lead‐free bullets, there was no radiographic evidence of bullets or fragments, indicating pass‐through shots. The greater cost per bullet and larger number of bullets required to kill a rabbit meant that using lead‐free bullets cost 6 times more per rabbit killed than using lead‐based bullets. The only commercially available lead‐free .22 LR bullets in Australia at the time of our study produced substantially poorer animal welfare outcomes, and were more expensive per killed rabbit, than lead‐based bullets. Lead‐free bullets designed to reduce lead exposure to scavenging wildlife and humans and should be assessed in terms of animal welfare outcomes and costs prior to being considered for widespread use. © 2020 The Wildlife Society. Abstract : The efficacy of lead‐free rimfire .22 LR bullets was compared with lead‐based bullets for shooting European rabbits in Australia. Lead‐free bullets were less effective, emphasizing the need for animal welfare testing for new ballistic technology.